(untitled) (International Journal of Engineering and Computer Science, 2024)
This work presents the software development lifecycle model applied on a rental product store system development. What motivates the idea of this work is the growing demand for rental stores that offer tools and other products, and the need for a system to manage and facilitate the rental process. This work aims to showcase an ideal software engineering implementation example. It also aims to meet the needs of the rental market and provide a technological solution to support and organize the operations of rental stores and customers. The study begins by defining and analyzing existing systems and comparing them to the proposed system using a comparison table. The proposed system includes functional and non-functional requirements and use case diagrams with descriptions and activity diagrams for each use case. The design phase includes an overall architecture, component diagram, and class diagram. The candidate solution pattern plan is used to compare various alternative patterns in order to come up with the most effective solution.